Rare forms of nonalcoholic fatty liver disease: hereditary lysosomal acid lipase deficiency - M. V. Mayevskaya; V. T. Ivashkin; M. S. Zharkova; T. P. Nekrasova; G. I. Ayusheva; R. V. Maslennikov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of review. To acquaint general practitioners with a rarely diagnosed disease - the hereditary deficiency of lysosomal acid lipase (DLAL) which can develop under the «mask» non-alcoholic fatty liver disease (NAFLD). Summary. There are two forms of DLAL clinical manifestations: as fulminant lethal Wolman disease and slowly progressing cholesterol ethers storage disease (CESD). This overview is devoted to more clinically relevant form of DLAL, significant for physicians and gastroenterologists - CESD which is often mistaken for NAFLD, however these diseases have different etiology, pathogenesis, pathomorphology and clinical course. Criteria of the clinical and pathomorphological differential diagnosis of DLAL and NAFLD are presented in the review, modern methods DLAL diagnosis confirmation and treatment perspectives are presented. Conclusion. Early detection of DLAL patients and adequate treatment can prevent development of the liver cirrhosis associated to this disease, as well as cardio-vascular complications.